1985
DOI: 10.1113/jphysiol.1985.sp015591
|View full text |Cite
|
Sign up to set email alerts
|

The contrast sensitivity of human colour vision to red‐green and blue‐yellow chromatic gratings.

Abstract: SUMMARY1. A method ofproducing red-green and blue-yellow sinusoidal chromatic gratings is used which permits the correction of all chromatic aberrations.2. A quantitative criterion is adopted to choose the intensity match of the two colours in the stimulus: this is the intensity ratio at which contrast sensitivity for the chromatic grating differs most from the contrast sensitivity for a monochromatic luminance grating. Results show that this intensity match varies with spatial frequency and does not necessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
497
8
17

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 876 publications
(561 citation statements)
references
References 26 publications
39
497
8
17
Order By: Relevance
“…The extent of the difference will depend on the relative degree of summation in colour receptive fields, and in the input stages of motion-detecting sub-units. Since both the spatial (Mullen, 1985) and the temporal (de Lange, 1958) sensitivity of colour detection mechanisms are low-pass we might expect a substantial degree of summation, and so a substantial enhancement in sensitivity for detection tasks over direction discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of the difference will depend on the relative degree of summation in colour receptive fields, and in the input stages of motion-detecting sub-units. Since both the spatial (Mullen, 1985) and the temporal (de Lange, 1958) sensitivity of colour detection mechanisms are low-pass we might expect a substantial degree of summation, and so a substantial enhancement in sensitivity for detection tasks over direction discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this form of stimulus should work with subjects who have impaired color vision. However, color may affect results with different SSVEP displays (Mullen, 1985;Regan, 1989;Arakawa et al, 1999).…”
Section: 1: Display Type and Gaze Shiftingmentioning
confidence: 99%
“…Even if it has been observed that pictures of natural scenes do have color information represented in medium to high spatial frequencies (Parraga et al, 1998), the visual system tends to perceive chromatic information at coarser scales better than luminance information (Mullen, 1985). 7 The reported effects of color should therefore arise from the spatial layout of crude color information.…”
Section: Figmentioning
confidence: 99%